Enhancing The Quality Of Non-Formal Education: A Study On Performance Management At PKBM Imam Syafe'i In Bandung Regency) - Rinny Iskandar; Meltarini, Meltarini; Marja Sinurat (Jurnal Scientia, 2024)
The high rate of school dropouts in Bandung Regency has prompted the government to promote PKBM (Community Learning Activity Centers) as a crucial alternative to mitigate this issue. This study aims to analyze the performance of non-formal education managers within these centers. Utilizing a qualitative research design with a descriptive approach, data were collected through observations, interviews, and document analysis. The analysis involved data reduction, data presentation, and conclusion drawing based on the Hoy &Miskel education management framework. The findings reveal that the Imam Syafe'i PKBM has demonstrated commendable performance by enhancing the quality of non-formal education. Challenges identified include insufficient literacy resources, students' limited technological proficiency, and restricted learning hours. Conversely, factors contributing to success include effective financial management, active collaboration with the Education Department and other institutions, and robust emotional support for students. Improvement efforts encompass expanding library collections, developing tutor internship programs, preparing pertinent learning materials, enhancing online learning validation and monitoring, administering efficient exams, and providing tutor training and certification. Nonetheless, several obstacles persist, such as inadequate library facilities and the necessity for a structured tutor internship model. Addressing these challenges involves augmenting library resources and establishing structured collaboration models for tutor internships with other institutions.